2017
DOI: 10.5539/jsd.v10n6p169
|View full text |Cite
|
Sign up to set email alerts
|

Household Waste Generating Factors and Composition Study for Effective Management in Gorkha Municipality of Nepal

Abstract: Municipal solid waste is a growing concern in cities of developing countries and households are the main contributor. Lack of reliable data sources remain one of the major drawbacks for deciding on effective waste management option. The study area Gorkha municipality is selected because it is one of the highly under-researched and least resource intensive municipalities in Nepal. However, continued growth in municipal waste if left unattended will only intensify the problem and thus demands proactive action. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
1
17
1
Order By: Relevance
“…Table 2 represents the comparison of MSW generation rate in the Baglung Municipality and other cities in the world. For instance, Gorkha (Maskey & Singh, 2017), Risikesh (Rawat & Daverey, 2018), Suzhou (Zhang et al, 2018) and Cape Haitian City (Philippe & Culot, 2009) have lower rate of waste generation whereas Takoradi (Miezah et al, 2015) and Mexicali City (Gomez et al, 2008) have higher household waste generation in comparison with this study. The household's generation rate of MSW is very high in Mexicali City (0.676 kg/c/d), which is a relatively developed city.…”
Section: Msw Generation Ratecontrasting
confidence: 48%
“…Table 2 represents the comparison of MSW generation rate in the Baglung Municipality and other cities in the world. For instance, Gorkha (Maskey & Singh, 2017), Risikesh (Rawat & Daverey, 2018), Suzhou (Zhang et al, 2018) and Cape Haitian City (Philippe & Culot, 2009) have lower rate of waste generation whereas Takoradi (Miezah et al, 2015) and Mexicali City (Gomez et al, 2008) have higher household waste generation in comparison with this study. The household's generation rate of MSW is very high in Mexicali City (0.676 kg/c/d), which is a relatively developed city.…”
Section: Msw Generation Ratecontrasting
confidence: 48%
“…The problem of waste in the world is also a concern, where the growing amount of waste production increased by 87.5%. Most waste production generally comes from low-middle-income countries and developing countries [7]. In processing waste, developing countries are still considered not entirely satisfactory, and this is because the existing processing system is not sufficient to process the waste produced, the amount of which is every year.…”
Section: Global Problemmentioning
confidence: 99%
“…In the study of waste composition and socio-economic factors influencing household waste generation in the Gorkha municipality in Nepal, Maskey and Singh (2017) employed a stratified sampling method and ordinary least square technique. The study revealed that 0.34kg/capita/day was generated by households in Gorkha and estimated generated household waste was 9.4 tonnes per day.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Secondly, unlike other studies ( Almasi et al., 2019 ; Foster et al., 2012 ; Chu et al., 2013 ; Buckingham et al., 2005 ; Maskey and Singh 2017 ; Sotamenou et al., 2019 ; Alhassan et al., 2020 ), this is the first that uses the multinomial logit model and exogenous switching effects treatment regression (ESTER) to model the effect of gender on the environment through waste disposal choices. Very crucial in this study rests on the observed and unobserved heterogeneity of household types.…”
Section: Introductionmentioning
confidence: 99%